BİBLİOMETRİC ANALYSİS OF STUDİES ON “GREEN FİNANCE” BASED ON WEB OF SCİENCE DATABASE (Third Sector Social Economic Review, 2024)
The main goal of this research is to examine articles that reconcile climate changes and green finance studies, which are frequently prominent in recent studies. The scope of the study is to conduct a bibliometric analysis of international articles written in the mentioned field. Articles written in the mentioned field and scanned in the Web of Science (WoS) database constitute the database of the study. Articles published in journals and scanned in the WoS database from the beginning of the study scope until 27/06/2023 were included. Articles published after the given date and scanned in the database were not included in the scope of the study. In this context, it was seen that there were 1060 studies identified in the database in question. When the studies were scanned with ""economy"" and ""business finance"" data as restrictive data, it was determined that 294 studies were conducted. As a result of the examination made by entering the relevant restrictive keys, it was seen that the first study in this field was published in 2010 and entered into the database. It has been observed that the country with the most publications on the subject included in the research area is the People's Republic of China. It has been determined that the author/s who published the most in this field are Taghizadeh-Hesary Farhad. It was noticed that the year with the most publications on the subject was 2022. It has been noticed that the most common publication type published in the field of research and included in the search is articles. It was determined that the journal that published the most articles and studies on the subject included in the research was the ""Energy Economics"" journal. In order to see the subject more clearly within the scope of the study, a network analysis was prepared using the VOSviewer mapping method, showing co-authorship relationships, showing the most refer-to-writer connections, and examining keyword correlations.
Keywords: Green Finance; Bibliometric Analyze; Vosviewer